2015
DOI: 10.1371/journal.pone.0121824
|View full text |Cite|
|
Sign up to set email alerts
|

A Maize Jasmonate Zim-Domain Protein, ZmJAZ14, Associates with the JA, ABA, and GA Signaling Pathways in Transgenic Arabidopsis

Abstract: Jasmonate (JA) is an important signaling molecule involved in the regulation of many physiological and stress-related processes in plants. Jasmonate ZIM-domain (JAZ) proteins have been implicated in regulating JA signaling pathways and the cross talk between various phytohormones. Maize is not only an important cereal crop, but also a model plant for monocotyledon studies. Although many JAZ proteins have been characterized in Arabidopsis and rice, few reports have examined the function of JAZ proteins in maize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
33
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 66 publications
(84 reference statements)
7
33
0
Order By: Relevance
“…Such differential expression patterns suggest that the transcription of these seven LaJAZ genes would subject to different regulatory mechanisms in L. aurea tissues. Similarly, previous studies also indicated that JAZ genes are differentially and constitutively expressed in different plant species such as rice [15], cotton [47], maize [48], rubber tree [49] and sugarcane [50]. Moreover, JAZ genes could be significantly induced by MeJA treatment [17,47,50,51].…”
Section: Plos Onementioning
confidence: 65%
“…Such differential expression patterns suggest that the transcription of these seven LaJAZ genes would subject to different regulatory mechanisms in L. aurea tissues. Similarly, previous studies also indicated that JAZ genes are differentially and constitutively expressed in different plant species such as rice [15], cotton [47], maize [48], rubber tree [49] and sugarcane [50]. Moreover, JAZ genes could be significantly induced by MeJA treatment [17,47,50,51].…”
Section: Plos Onementioning
confidence: 65%
“…As a typical JAZ protein, GhJAZ2 contains a ZIM domain and a C‐terminal Jas domain, interacts with GhCOI1 and can be degraded by exogenous MeJA (Figs and S1C). Although the Jas domain has been proposed to play an important role in the degradation of JAZ proteins, increasingly, reports have shown that the overexpression of JAZ can repress JA signalling whether or not it contains the Jas domain (Yang et al ., ; Zhou et al ., ). Overexpression of GhJAZ2 reduces the sensitivity to JA in cotton and impairs the resistance to V. dahliae and insect herbivory, in spite of the instability of GhJAZ2 in cells containing high levels of JAs (Figs , 2 and S2).…”
Section: Discussionmentioning
confidence: 97%
“…As a typical JAZ protein, GhJAZ2 contains a ZIM domain and a C-terminal Jas domain, interacts with GhCOI1 and can be degraded by exogenous MeJA (Figs 3 and S1C). Although the Jas domain has been proposed to play an important role in the degradation of JAZ proteins, increasingly, reports have shown that the overexpression of JAZ can repress JA signalling whether or not it contains the Jas domain Zhou et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…TIFY family proteins can be classified into 4 subfamilies based on their constituent domains [ 40 ]: TIFY subfamily, containing only the TIFY (ZIM) domain; ZML (ZIM-like) subfamily, containing the TIFY, CCT and ZML domains; JAZ subfamily, containing the TIFY and Jas domains (also called the CCT_2 domain); and PPD subfamily, containing the TIFY domain and a truncated Jas domain. The TIFY family plays a role in regulating diverse biological processes in plants, including elongation of the petiole and hypocotyls [ 42 ], root growth [ 43 ], flower abscission [ 44 ], leaf development [ 45 ] and responses to abiotic and biotic stress [ 46 48 ].…”
Section: Discussionmentioning
confidence: 99%